Effectiveness of a School Smartphone Ban in Reducing Cyberbullying and Supporting a Safe Learning Environment: A Descriptive–Evaluative Study in Indonesia - ATR Rosa; Lea Trliyah; Netti Susanti; Ati Rahmawati; Agriyosda Syeftia (Journal of Basic Education Research, 2026)
Purpose of the study: This study evaluates the effectiveness of a school-wide smartphone-ban policy in reducing cyberbullying among junior high school students and identifies the factors that support or hinder its implementation in two public junior high schools in the Bandung area, Indonesia. Methodology: A quantitative descriptive–evaluative design was used. Data were collected from junior high school students at SMP Negeri 35 Bandung and SMP Negeri Satu Atap Nagrog through a four-point Likert-scale questionnaire covering six effectiveness indicators, complemented by structured observation. The sample was drawn using the Slovin formula and analysed using descriptive statistics and an effectiveness-percentage classification. Main Findings: A majority of respondents reported that the ban was consistently enforced (69.14%) and that cyberbullying incidents had declined after its introduction (61.73%). The composite effectiveness score was 78.67%, which falls in the “effective” category. Restricting in-school smartphone access reduces the opportunity structure for cyberbullying, but the effect is conditioned by student compliance and the consistency of school supervision. Novelty/Originality of this study: While the international literature on school phone bans focuses largely on academic performance and general well-being, this study foregrounds cyberbullying as the primary outcome and provides school-level evidence from the under-represented Indonesian context, framed through an input–process–output–outcome systems lens.